1989
DOI: 10.2307/3759705
|View full text |Cite
|
Sign up to set email alerts
|

Production of Phenol Oxidases and Peroxidases by Wood-Rotting Fungi

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 157.182.150.22 on Sun, 12 Apr 2015 15:36:20 UTC All use subject to JSTOR Terms and Conditions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1
21

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(65 citation statements)
references
References 3 publications
0
43
1
21
Order By: Relevance
“…Peroxidase and laccase activities were determined by the oxidation of 0-dianisidine (∈460 = 29.400 M -1 cm -1 ) with and without the adding of hydrogen peroxide (16). The Manganese Peroxidase activity was determined by the phenol red oxidation (∈610 = 4.460 M -1 cm -1 ) (5).…”
Section: Enzymatic Assaysmentioning
confidence: 99%
“…Peroxidase and laccase activities were determined by the oxidation of 0-dianisidine (∈460 = 29.400 M -1 cm -1 ) with and without the adding of hydrogen peroxide (16). The Manganese Peroxidase activity was determined by the phenol red oxidation (∈610 = 4.460 M -1 cm -1 ) (5).…”
Section: Enzymatic Assaysmentioning
confidence: 99%
“…A schematic representation of the strategies employed to distinguish between individual phenol-oxidizing enzymes by subtractive activity assays (Szklarz et al, 1989) and sequential enzymatic staining of gels using native-PAGE is shown in Fig. 1.…”
Section: Enzyme Assaymentioning
confidence: 99%
“…MnP determinations were based on the oxidation of phenol red, according to Kuwahara et al (19). Laccase was determined via the H2O2-independent oxidation of syringaldazine (ethanol solution) to its quinone form (21). The supernatants were obtained following centrifugation of the content of whole flasks at 17,000 rpm for 30 min at 5ºC.…”
Section: Enzyme Assaysmentioning
confidence: 99%